Firm’s Characteristics and Firm Performance: Evidence from Non-Financial Companies in Nigeria - GBADEBO, Akindele (Acta Universitatis Danubius. Œconomica, 2022)
This study set out to examine the impact of firm characteristics on firm performance of non-financial companies listed on the Nigerian exchange group. . The sample for this research consisted of the 113 non-financial global firms that were listed on the Nigeria Exchange Group as of March 5, 2021. Purposeful selection was used to choose 76 Nigerian firms with a focus on non-financial services that are listed on foreign stock markets. The study looked at information from businesses' annual reports over a period of 11 years using the Generalized Method of Moments (GMM) estimate (2010-2020). Some of the aspects of businesses that are examined include: size (FSIZE), age (FAG), growth rate (GRATE), financial leverage (FLR), liquidity (LQ), free cash flow (FCF), business risk (BR), tangibility of assets (ATANG), and value added productivity (VAP) (VAP). The use of least squares multiple regression on panel data allowed us to evaluate the hypotheses. The GMM estimator found that firm size (= 0.0251), liquidity (= 0.1534, p-value = 0,023), and assets tangibility (= -0,3021, p-value = 0.017) all have positive and statistically significant relationships with DPR, while the age of the business (= -0.061, p-value = 0.615) has a negative but not statistically significant effect on VAP. Positive correlations were also found between other factors like growth rate, financial leverage, free cash flow, and business risk and the VAP of the sampled companies, but these correlations were not statistically significant (= 0.0743, p-value =0.125, =0.1144, p-value =0.512, =0.0016, p-value=0.612, =0.0041, p-value =0.517). Findings from this study imply that in order to boost their businesses' performance, managers of publicly traded Nigerian non-financial organizations should pay close attention to the firm size, liquidity, business growth and tangibility of their firms' assets.